Humoral protection against mosquito bite-transmitted Plasmodium falciparum infection in humanized mice. (December 2017) - Sack, Brandon; Mikolajczak, Sebastian; Fishbaugher, Matthew; Vaughan, Ashley; Flannery, Erika; Nguyen, Thao; Betz, Will; Jane Navarro, Mary; Foquet, Lander; Steel, Ryan; Billman, Zachary; Murphy, Sean; et al.
Abstract A malaria vaccine that prevents infection will be an important new tool in continued efforts of malaria elimination, and such vaccines are under intense development for the major human malaria parasitePlasmodium falciparum (Pf ). Antibodies elicited by vaccines can block the initial phases of parasite infection when sporozoites are deposited into the skin by mosquito bite and then target the liver for further development. However, there are currently no standardized in vivo preclinical models that can measure the inhibitory activity of antibody specificities againstPf sporozoite infection via mosquito bite. Here, we use human liver-chimeric mice as a challenge model to assess prevention of naturalPf sporozoite infection by antibodies. We demonstrate that these mice are consistently infected withPf by mosquito bite and that this challenge can be combined with passive transfer of either monoclonal antibodies or polyclonal human IgG from immune serum to measure antibody-mediated blocking of parasite infection using bioluminescent imaging. This methodology is useful to down-select functional antibodies and to investigate mechanisms or immune correlates of protection in clinical trials, thereby informing rational vaccine optimization. Malaria: 'Humanized' mice offer a new preclinical research tool Mice containing human liver cells can model early-stage malaria infection and test antibody efficacy. A major obstacle in malaria vaccine development is the lack of relevant preclinical models to study how to prevent malaria infection. Stefan Kappe, of the United States' Center for Infectious Disease Research and the University of Washington, led a collaboration of American and Dutch scientists to overcome this using mice in which the mouse liver cells have been largely replaced with human liver cells. The group demonstrated that their model mirrors infection with the malaria-causing parasitePlasmodium falciparum from mosquito bite through the week-long liver development, and harnessed this to discern the efficacy of different antibodies against the parasite. This research could hugely benefit our understanding of malaria infection and reduce the high failure rate of human vaccine clinical trials.